2000
DOI: 10.2114/jpa.19.249
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-day Effects of Ethanol Consumption on EEG Topography and Cognitive Event-related Potential in Adult Males.

Abstract: Time-of-day effects of ethanol consumption on EEG topography and cognitive event-related potential in adult males were studied. Ethanol (0.5 g/kg) or control drink was orally administered to nine healthy males at 10:00 and 18:00. The alpha2 amplitude was significantly lower than that of the control at 0.5, 2.5 and 4.5 hours after ethanol consumption in the morning. These effects were observed in the left hemisphere and were only f o un d a ft e r c o n su m p t i o n i n th e m o r n i ng . T h e subjectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…For example, recent electrophysiological recordings observed time-of-day effects of ethanol consumption on EEG topography. In a study investigating the effects of ethanol on the P300 event-related potential, Liu et al (2000) could show a decrease of the ␣2-amplitude in the morning but not in the evening. Conversely, the P300 amplitude was lowered in the evening but not in the morning.…”
Section: Genetic Variations Of Human Clock Genes Are Associated With mentioning
confidence: 96%
See 1 more Smart Citation
“…For example, recent electrophysiological recordings observed time-of-day effects of ethanol consumption on EEG topography. In a study investigating the effects of ethanol on the P300 event-related potential, Liu et al (2000) could show a decrease of the ␣2-amplitude in the morning but not in the evening. Conversely, the P300 amplitude was lowered in the evening but not in the morning.…”
Section: Genetic Variations Of Human Clock Genes Are Associated With mentioning
confidence: 96%
“…In humans, chronic alcoholism is associated with dramatic disruptions in sleep and other circadian biological rhythms, including body temperature, blood pressure, metabolism, hormone secretion, and EEG topography (Brower, 2001;Devaney et al, 2003;Fonzi et al, 1994;Imatoh et al, 1986;Kawano et al, 2002;Kodama et al, 1988;Liu et al 2000, Mukai et al, 1998Numminen et al, 2000;Sano et al, 1993;Schmitz et al, 1996). These wide-spread chronobiological disruptions are similar to those associated with mood disorders (Rosenwasser and Wirz-Justice, 1997), and, indeed, mood dysregulation is a hallmark of alcohol withdrawal (Driessen et al, 2001).…”
Section: Circadian Rhythms and Cellular Clocksmentioning
confidence: 99%
“…Unfortunately, ethanol, unlike most other psychoactive substances, is not linked to any particular receptors in specific brain areas, thus making it more difficult to determine which brain mechanisms are most likely to be vulnerable to alcohol intoxication. Indeed, studies in humans and rodents have mainly shown a general reduction in cortical activity due to ethanol (Davies and Alkana 2001;Wang et al 1999;Krull et al 1994;Liu et al 2000). However, the underlying physiological structures that are relevant to our study can be linked to different modules of the theoretical framework introduced above.…”
Section: Introductionmentioning
confidence: 98%
“…Alcohol: In humans, chronic alcohol intake is associated with sleep disturbance and alterations in various daily physiological rhythms, including blood pressure, body temperature, metabolism, hormone secretion, and EEG topography [256][257][258][259][260][261]. Similar chronobiological disruptions were observed in patients with mood disorders [262].…”
Section: Drugs That Bind To Ionotropic Receptors and Ion Channelsmentioning
confidence: 98%